Female Entrepreneurship and Women’s Empowerment in Footwear Manufacturing Mypes in the Industrial Park of Villa El Salvador, Lima – Peru - Perez Ramos, Geraldine Wendy; Marcelo Quispe, Luis Alberto; Gasparrini Cañas, Víctor Gerardo; Saldaña Narro, Julio Brayan; Olórtegui Alcalde, Luis Miguel (LACCEI, 2025)
The main purpose of the study was to analyze the level of association between female entrepreneurship and women’s empowerment in small and medium-sized enterprises (Mypes) in the footwear sector of the industrial park in Peru. This research is quantitative, basic, with a non-experimental cross-sectional design and a correlational level. A census sample consisting of thirty female entrepreneurs in this sector was used, and two questionnaires were applied: one to measure the female entrepreneurship variable with twenty-seven items, and another to measure the women’s empowerment variable with twenty-seven items. Both instruments demonstrated extremely high reliability, with Cronbach’s alpha coefficients of 0.881 and 0.895, respectively. The statistical results showed a high and significant association (Rho=0.862; p